Effects of a rule change that eliminates body-checking on the relative age effect in Ontario minor ice hockey - Hancock, D. J.; Young, B. W.; Ste-Marie, D. M. (Journal of Sports Sciences, 2011)
Relative age effects in sport reflect an over-representation of athletes born early in a selection year that lead to selection and performance advantages. These effects might be enhanced by rules that increase physicality. An opportunity to investigate these influences arose when Hockey Canada altered its body-checking rules. Two studies are described that investigate the possible influence of this rule change. Study 1 used cross-sectional data to contrast relative age effects for 9-year-olds in games with and without body-checking (birth quartile 1 ranged from 27 to 39%; birth quartile 4 from 10 to 20%). Study 2 used quasi-longitudinal data to examine age effects when players transitioned from a season in which body-checking was permitted to one that prohibited such checking (birth quartile 1 ranged from 27 to 39%; birth quartile 4 from 11 to 20%). Chi-square statistics demonstrated relative age effects in both studies irrespective of body-checking. Post-hoc analyses indicated reductions in these effects that were limited to some second and third quartiles when body-checking was prohibited. Body-checking is not a critical mechanism of relative age effects. The physicality of ice hockey, regardless of body-checking, and increased experience in ice hockey are influential.